2022
DOI: 10.3390/biom12091312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RIPC on the Metabolome in Patients Undergoing Vascular Surgery: A Randomized Controlled Trial

Abstract: Background: remote ischemic preconditioning (RIPC) is a phenomenon in which short episodes of ischemia are applied to distant organs to prepare target organs for more prolonged ischemia and to induce protection against ischemia-reperfusion injury. This study aims to evaluate whether preoperatively performed RIPC affects the metabolome and to assess whether metabolomic changes correlate with heart and kidney injury markers after vascular surgery. Methods: a randomized sham-controlled, double-blinded trial was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A clear understanding of rIPC may contribute to evaluating its role in preventing ischemia-related organ injury, while the exact mechanisms of rIPC remain unclear. 24 Previous studies suggested that humoral and neuronal mechanisms, circulating immune cells, and hypoxia-induced gene activation may contribute to its effects. 25 Tong and colleagues reported that rIPC can significantly increase humoral stromal cell-derived factor-1 alpha (hSDF-1α) levels in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A clear understanding of rIPC may contribute to evaluating its role in preventing ischemia-related organ injury, while the exact mechanisms of rIPC remain unclear. 24 Previous studies suggested that humoral and neuronal mechanisms, circulating immune cells, and hypoxia-induced gene activation may contribute to its effects. 25 Tong and colleagues reported that rIPC can significantly increase humoral stromal cell-derived factor-1 alpha (hSDF-1α) levels in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A significant decrease in glutamate levels during maximal ischemia and 24 h hours after lower limb surgery (−29% and −51%, respectively) has been described earlier, indicating that glutamate usage is upregulated both during and after ischemia [ 25 ]. Elevated glutamate levels following RIPC have been previously observed in both human and animal studies, implying an enhancement in energy metabolism to accommodate increased demand [ 21 , 26 , 27 ]. Our results align with these findings, as a significant change in glutamate levels was noted between the groups, with levels only reduced in the sham group.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, similar patients undergoing vascular surgery did not exhibit significant changes in lysoPCs and PCs. This may be due to the greater metabolic disturbance from open surgery compared to the relatively less invasive stent placement procedure [ 13 , 26 , 34 ]. As the research of lysoPCs used as signal molecules is still scarce, further studies are needed to fully comprehend the changes and pathways seen in the RIPC group.…”
Section: Discussionmentioning
confidence: 99%